Drift-Diffusion Analysis of Neutrophil Migration during Inflammation Resolution in a Zebrafish Model. (17th May 2012) - Holmes, Geoffrey R.; Dixon, Giles; Anderson, Sean R.; Reyes-Aldasoro, Constantino Carlos; Elks, Philip M.; Billings, Stephen A.; Whyte, Moira K. B.; Kadirkamanathan, Visakan; Renshaw, Stephen A.
Abstract : Neutrophils must be removed from inflammatory sites for inflammation to resolve. Recent work in zebrafish has shown neutrophils can migrate away from inflammatory sites, as well as die in situ. The signals regulating the process of reverse migration are of considerable interest, but remain unknown. We wished to study the behaviour of neutrophils during reverse migration, to see whether they moved away from inflamed sites in a directed fashion in the same way as they are recruited or whether the inherent random component of their migration was enough to account for this behaviour. Using neutrophil-driven photoconvertible Kaede protein in transgenic zebrafish larvae, we were able to specifically label neutrophils at an inflammatory site generated by tailfin transection. The locations of these neutrophils over time were observed and fitted using regression methods with two separate models: pure-diffusion and drift-diffusion equations. While a model hypothesis test (the F -test) suggested that the datapoints could be fitted by the drift-diffusion model, implying a fugetaxis process, dynamic simulation of the models suggested that migration of neutrophils away from a wound is better described by a zero-drift, "diffusion" process. This has implications for understanding the mechanisms of reverse migration and, by extension, neutrophil retention at inflammatory sites.